Successful pregnancy outcome in patient with Pompe disease despite discontinuation of enzyme replacement therapy - Dunja Leskovar Lemešić; Dražen Perica; Gordan Zlopaša; Biserka Knezić Frković; Nediljko Šućur; Željko Reiner; Ivan Pećin (European Journal of Case Reports in Internal Medicine)
Background: Pompe disease (PD), is an autosomal recessive metabolic disorder caused by mutations in the acid alpha-glucosidase (GAA) gene, resulting in a deficiency of the same enzyme and glycogen buildup in tissues. Late onset PD (LOPD) is characterized by muscle illness, accompanied by diaphragmatic involvement and leading to respiratory insufficiency. Fortunately, the disease progresses slowly, and treatment with enzyme replacement therapy can further delay its development. Pregnancy in women with LOPD requires special caution because musculoskeletal changes and greater physical demands may worsen muscular weakness and endanger both the mother and unborn child. Although several cases of pregnant women with LOPD that continued enzyme replacement therapy (ERT) during pregnancy have been reported, there is still a lack of data regarding teratogenicity and safety of the foetus. Case report: We present a case of a 31-year- old pregnant women with a mild form of LOPD who discontinued ERT during whole pregnancy. During the whole pregnancy there were no clinical signs of progression of muscle or pulmonary weakness. With careful monitoring of the patient and foetus, and planned delivery, a healthy baby girl was born. ERT was reintroduced 6 months after delivery with premedication (corticosteroids and antihistamines) for the first application, with no allergic reaction noted. Conclusion: In this patient with well-controlled LOPD, ERT was safely discontinued during pregnancy without disease worsening. The risks of ERT in pregnancy outweighed the potential complications of well-controlled disease. The final decision should be made with an individual approach for each patient by a multidisciplinary team.